The Impact of the Argument-Driven Inquiry (ADI) Instructional Model on Biodiversity Topics to Enhance Students' Argumentation Skills - Melta, Defrian; Razak, Abdul; Yohandri, Yohandri (Bioedunis Journal, 2024)
This study aims to investigate the impact of Argument-Driven Inquiry (ADI)-based biology instruction on students' argumentation skills in the context of biodiversity. The research is classified as a quasi-experimental study using a pretest-posttest nonequivalent control group design. The independent variable in this study is the implementation of the Argument-Driven Inquiry (ADI) instructional model. The population of this study comprises all tenth-grade students at SMAN 5 Padang. The sample consists of two classes, with Class X IPA 1 selected as the experimental group and Class X IPA 2 as the control group. Data on students' argumentation skills were collected using essay-type tests. The data analysis techniques employed include the Mann-Whitney U test, Wilcoxon Signed-Rank test, Independent Sample t-test, and Effect Size test. The results indicate that the use of the Argument-Driven Inquiry (ADI) instructional model positively influences the improvement of students' argumentation skills on the topic of biodiversity. This implies that students successfully achieved the targeted learning objectives using the ADI model.